Understanding the conditions for inclusive education: A realist evaluation of a French territorial innovation - Eléonore Ségard; Olivier Aromatario; Philippe Chervin; Linda Cambon (PLoS ONE, 2026)
Article 24 of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) calls for inclusive education systems. Despite this mandate, collaboration between schools and specialized services often remains limited. This study examined the systemic conditions that enable effective inclusion, extending beyond pedagogical approaches through a complexity-informed framework. Using a realist evaluation, the research investigated an innovative inclusive education initiative implemented in the Eure-et-Loir district in France for children and young people with neurodevelopmental disabilities (CYWD). The study sought to identify the mechanisms that foster autonomy and social participation among CYWD and to determine the conditions under which these mechanisms emerge. Two cases—one in a primary school and one in a secondary school—were analyzed. In total, 47 semi-structured interviews were conducted with 63 participants (CYWD, classmates, families, specialized professionals, national education staff, and school life personnel). The analysis identified 162 ingredients across four domains: the district-level inclusive education scheme, the National Education system, the Specialized system, and their interinstitutional cooperation. These ingredients were combined into 15 success conditions that activate five key mechanisms within CYWD: developing a sense of safety and stability, feeling fully part of the class, recognizing and using accommodations, motivation to learn, and motivation to engage socially. These mechanisms contributed to learning progress (often developing in unexpected ways), greater autonomy, increased initiative, and richer peer participation, including outside the classroom. Broader systemic benefits were also observed, including a general climate of kindness in schools and increased empowerment among families. The study demonstrates that high-commitment inclusive education practices can be implemented at a district level and are perceived to have a positive impact on CYWD. It identifies key systemic and collaborative configurations that can guide the development and transferability of effective inclusive education practices across diverse contexts.